Teacher empowerment through curriculum development : theory into practice - CARL, Arend E. Cape Town, 2009 3rd ed 2009.; Juta and Company(Pty) Ltd; Bible Society of South Africa; CARL, Arend E. Cape Town, 2009 3rd ed 2009.; Juta and Company(Pty) Ltd; Bible Society of South Africa (Cape Town: Juta, 2009)
"Teacher Empowerment through Curriculum Development: Theory into Practice encourages the empowerment and involvement of teachers in the curriculum development process. This updated third edition is a must for every teacher who acknowledges the need for empowerment and wishes to contribute to the process of curriculum development in a changing South Africa."--Jacket
Includes bibliographical references and index.
Adult
Keywords: Arend E Carl -- 2003.; Juta and Company(Pty) Ltd; Always learning; Kabbala; Teacher participation in curriculum; Curriculum planning; South Africa; Adult Non-Fiction